Maternal and Neonatal Outcomes Related to Iron Deficiency Anemia and Serum Ferritin Status: A Multicenter Prospective Study From Eastern Marmara, Turkey - Çiğdem PULATOĞLU; Derya BAŞBUĞ; Bertan AKAR; Hayal ŞİMŞEK; Pınar ÇAKIR; Alper BAŞBUĞ; Eray ÇALIŞKAN (Namık Kemal Tıp Dergisi, 2019)

(untitled)
Aim:The aim was to evaluate the incidence of iron deficiency anemia in pregnancy in the East Marmara region of Turkey in order to determine its prevalence along with the effects and associations of iron supplementation on maternal and neonatal outcomes.Materials and Methods:This study was conducted in six centers and included a total of 1102 pregnant women. Blood samples were collected for hematological status and serum ferritin levels during pregnancy, and the adverse maternal and perinatal outcomes were determined. Iron deficiency anemia was diagnosed according to the World Health Organization criteria as hemoglobin level of < 11 g/dl and ferritin level of <15 μg/dL.Results:The rate of anemia was 19.8%, with 44% of them receiving iron supplementation. The maternal age was lower in the anemic group (26.5 vs. 27.7, p = 0.01). Selective iron use was more frequent in the anemic group, while routine iron use was more frequent in the non-anemic group (47.1% vs. 29.3%; p = 0.01).Conclusion:Iron deficiency anemia is a frequent problem in pregnancy. However, many anemic pregnant women do not receive iron therapy. Iron supplementation may have positive effects on maternal and perinatal outcomes. In order to combat iron deficiency anemia in pregnancy, wide spread use of iron supplements should be established.